2014
DOI: 10.1108/jcm-06-2014-1003
|View full text |Cite
|
Sign up to set email alerts
|

Application of regulatory focus theory to search advertising

Abstract: Purpose The purpose of this paper is to test the utility of regulatory focus theory principles in a real-world setting; specifically, Internet hosted text advertisements. Effect of compatibility of the ad text with the regulatory focus of the consumer was examined. Design/methodology/approach Advertisements were created using Google AdWords. Data were collected for the number of views and clicks each ad received. Effect of regulatory fit was measured using logistic regression. Findings Logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
0
18
1
1
Order By: Relevance
“…The results show that regulatory fit plays a significant role for prevention-focused consumers and leads to higher purchase intention. However, contrary to earlier findings (Higgins, 2005;Mourali & Pons, 2009;Mowle et al, 2014), in the case of the promotion-focused consumers, regulatory nonfit plays a significant role.…”
Section: General Discussion and Implicationscontrasting
confidence: 99%
See 1 more Smart Citation
“…The results show that regulatory fit plays a significant role for prevention-focused consumers and leads to higher purchase intention. However, contrary to earlier findings (Higgins, 2005;Mourali & Pons, 2009;Mowle et al, 2014), in the case of the promotion-focused consumers, regulatory nonfit plays a significant role.…”
Section: General Discussion and Implicationscontrasting
confidence: 99%
“…Kim and Sung's (2013) research in the context of advertising, using Gucci as a sophisticated and Old Navy as a sincere brand, demonstrates that the promotion-framed message is more persuasive when advertising a sophisticated brand, whereas the prevention-framed message is more persuasive when advertising a sincerity brand. Similarly, Mowle et al (2014) reveal that when the frame of a message is compatible with an individual's regulatory focus, there is a larger tendency to click on an online advertisement. Thus, prior research suggests that compatibility of regulatory focus and goal orientation (regulatory fit) drives decision-making.…”
Section: The Effect Of Regulatory Fitmentioning
confidence: 99%
“…The concept of regulatory focus therefore makes it possible to examine individuals regarding processes of goal setting and attainment, which has proven to be useful in various domains. For example, in marketing and consumer psychology it allows for the adaptation of advertisements to the particular focus of the recipient (Mowle et al, 2014 ). Conversely, advertisements can be generated specifically to suggest a certain regulatory focus to recipients and influence decision processes by such means (Micu and Chowdhury, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…By using consumers’ past online behavior to identify their dominant regulatory focus, companies could deliver customized messaging that dynamically creates conditions of regulatory fit based on each consumer's unique preferences. Such an approach has been tested on a small scale using online search advertising (Mowle, Georgia, Doss, & Updegraff, ). Although the study's results revealed a main effect of promotion focus, participants were twice as likely to click on a Google search advertisement when its message fit their keyword‐defined regulatory focus.…”
Section: Types Of Regulatory Fitmentioning
confidence: 99%